Fenomena Pergeseran Konflik Pemikiran Islam dari Tradisionalis vs Modernis ke Fundamentalis vs Liberalis - Huda, Khoirul (Program Pascasarjana UIN Sunan Ampel Surabaya, 2009)
A new mode of religious conflict has emerged in Indonesia following the fall of the old regime in the country. The conflict in point is that between the fundamentalists and the liberals, one that means that the nuance of the conflict is no longer organizational any more than it is ideological. We now rarely hear about the conflicts between the traditionalists and the modernists, just as we now rarely are capable of differentiating their basic tenets. The difference between the two has now become to a large extent vague. In the meantime, conflicts are now taking place between the fundamentalists and the liberals on almost regular basis. Hence, we hear the conflict for example between the FUUI and Ulil Abshar Abdalla who received death threat from the afro-mentioned organization. And also the so-called Monas Tragedy, which for some reflects the real tension between the two currents of thought. This paper is designed to analyze this conflictual phenomenon and the implication that may emerge thereof by using the Poststructural theory, which is the continuation of the structuralist theory of Levi-Strauss. What we mean by the Post-structural theory is that which is developed by Michel Foucault (d. 1984) where he speaks of the archeology of knowledge and the genealogy of power. In Foucaultâs theory, the former is to do with the organization of documents, their classification, their distribution and management in an orderly manner so as to enable us to differentiate between which are relevant and which are not. This theory is also about describing the so-called relations among elements of social phenomena. The latter in the meantime is to do with the analysis of the historical relationship between power and discourse. It concerns with the analysis of the trajectories of a discourse and its practices, and its relationship with what he calls the regime of truth that claims to have the pseudonaturalistic and global implication. This theory deals with the mode of relationship between these two domains. Hence, while this paper is mainly concerned with the religious thought, it is inevitably related to the notion of politics and power.